Exploring Neuro-Linguistic programming (NLP) Techniques for Reducing Public Speaking Anxiety: A Study of Practitioner Approaches during Training - Robing Robing; Eska Dirga; Ariandi Zulkarnain (Berumpun: International Journal of Social, Politics, and Humanities, 2022)
The application of Neuro-Linguistic Programming (NLP) techniques has garnered attention as a prospective method for mitigating speaking anxiety in public. This research investigates the utilisation of neuro-linguistic programming (NLP) techniques by a proficient instructor within the framework of the 'Art of Public Speaking' training program, with the primary objective of alleviating the anxiety linked to delivering speeches to a public audience. The current study was conducted at Cita Dines Hotel Makassar on August 4th, 2022. The methodology employed in this study encompassed a thorough gathering of data, which was achieved by actively participating as a trainer assistant, employing observational techniques, conducting detailed interviews, and carefully documenting the training sessions. The collected data underwent a rigorous analytical process guided by Burn's theory on Neuro linguistic Programming. This theoretical framework encompasses various strategies, such as rapport, Flexibility, Outcomes and VAKOG model (Visual, Auditory, Kinesthetic, Olfactory, Gustatory). The proficient incorporation of these NLP tactics by the trainer not only emphasised their importance but also demonstrated their efficacy in improving the quality of training sessions and promoting meaningful interpersonal connections. This study provides insights into the practical implementation of neuro linguistic programming (NLP) techniques and their capacity to improve the difficulties commonly encountered in public speaking.